Policy Analysis of Sustainable Tourism Destination Management Organization (DMO) in 10 Countries with the Best Tourism Version of the Travel & Tourism Development Index - Ulfa, Haurani (Riwayat: Educational Journal of History and Humanities, 2023)
Good tourism management will improve the welfare of the community in the tourism destination area. The relationship between the competitiveness of tourist destinations, will have an impact on sustainable tourism. The goal of creating competitiveness is to gain and expand market share both domestically and internationally by participating in ensuring that the availability of resources supporting tourism is used efficiently and sustainably. Along with the demands for sustainable tourism competitiveness, especially in ASEAN countries, it shows that competitiveness and sustainability have a reciprocal relationship and support each other. Therefore, a DMO (Destination Management Organization) is needed which has the function of leading and coordinating elements of the destination (attractions, amenities, accessibility) and a sustainable environment (sustainable)